Everyday desistance: the transition to adulthood among formerly incarcerated youth - Abrams, Laura S. (Critical issues in crime and society, 2017)
"In Everyday Desistance, Laura Abrams and Diane J. Terry examine the lives of young people who spent considerable time in and out of correctional institutions as adolescents. These formerly incarcerated youth often struggle with the onset of adult responsibilities at a much earlier age than their more privileged counterparts. In the context of urban Los Angeles, with a large-scale gang culture and diminished employment prospects, further involvement in crime appears almost inevitable. Yet, as Abrams and Terry point out, these formerly imprisoned youth are often quite resilient and can be successful at creating lives for themselves after months or even years of living in institutions run by the juvenile justice system. This book narrates the day-to-day experiences of these young men and women, focusing on their attempts to surmount the challenges of adulthood, resisting a return to criminal activity, and formulating long-term goals for a secure adult future"--Provided by publisher